ANALISIS FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2020) - Larassari Larassari; Dedik Nur Triyanto (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Going concern audit opinion is important information for users of financial statements, especially for investors who make decisions in investing because this is a warning that there are indications that the company will go bankrupt. The purpose of this study was to determine the factors that can affect the provision of going concern audit opinions using indicators of company growth, debt default, liquidity and opinion shopping in mining sector companies listed on the Indonesia Stock Exchange in 2016-2020. This study uses quantitative methods. The purposive sampling technique used in this study was to obtain a sample of 34 companies or 170 data samples. The analytical method of this research is logistic regression analysis using IBM SPSS Statistic software version 25. Data collection uses secondary data sources from the annual financial statements of mining sector companies listed on the Indonesia Stock Exchange in 2016-2020. Based on the results of this study, company growth, debt default, liquidity and opinion shopping have a simultaneous effect on the provision of going concern audit opinions. Partially, liquidity has a negative effect on going concern audit opinion. Company growth, debt default and opinion shopping have no partial effect on going concern audit opinion. Based on these results, investors are advised to pay attention to the level of liquidity or the company's ability to meet its short-term obligations to minimize the risk of indications of bankruptcy before investing in investing